Level of Knowledge, Attitude, and Behaviour of Cattle Farmers Towards Anthrax Disease in Tileng Village, Kapanewon, Girisubo, Gunungkidul Regency - Narendra Desta Eryanta; Engkus Ainul Yakin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Anthrax is a serious infectious illness affecting ruminant animals and also poses a risk to humans. Incidents of Anthrax have been reported in the Girisubo District of Gunungkidul Regency at the beginning of 2025. The initial action in preparing to stop the spread of Anthrax is addressed. This research seeks to evaluate the knowledge, attitudes, and behaviors of cattle farmers about Anthrax in Tileng Village, located in the Girisubo District of Gunungkidul Regency. A survey method was employed for this study, with 125 cattle farmers from Tileng Village participating. Information regarding farmers' knowledge, attitudes, and behaviors towards Anthrax was gathered through a questionnaire. The analysis of the data utilized descriptive statistics to assess the connections among knowledge, attitudes, and behaviors. The findings reveal that cattle farmers in Tileng Village, Girisubo District, Gunungkidul Regency possess a considerable understanding of Anthrax, with 112 farmers (87.2%) showing good knowledge. Additionally, 20 farmers (16%) displayed good attitudes, and 30 farmers (24%) exhibited appropriate behaviors regarding Anthrax. Only 5 farmers (4%) were identified as having strong knowledge, attitudes, and behaviors concerning Anthrax. This research highlights that while most cattle farmers in Tileng Village have solid knowledge, their attitudes and behaviors towards the Anthrax disease remain at a moderate level.